Application of Blockchain Technology in Energy Trading: A Review - Li, Hongbiao; Xiao, Fan; Yin, Lixin; Wu, Fengtong (Frontiers in Energy Research, 2021)
As blockchain and energy trading have become hot topics in industry and academia, this paper presents brief literature regarding blockchain-based energy trading in the fields of energy trading with blockchain. At first, the background and development process is presented, and then the applications of Blockchain in Energy Trading are surveyed and analyzed. And finally, conclusions are summarized and important directions are highlighted in this field.